A glass fiber reinforced modified polyolefin plastic and preparation method thereof

By adding organic phosphorus nitrogen to polyolefin plastics and adopting specific mixing and granulation processes, the problem of insufficient mechanical strength and flame retardant and fire-retardant properties of polyolefin plastics is solved, achieving a comprehensive improvement in performance and a wider application range.

CN119241952BActive Publication Date: 2025-03-04SHANDONG JIANA ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411773874.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-04
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing glass fiber reinforced modified polyolefin plastics have shortcomings in terms of mechanical strength and flame retardant fire resistance, which limits their application in the high-performance field.

Method used

By preparing organic phosphorus-nitrogen modified glass fibers and mixing them with polyolefin resin, compatible agent, lubricant, antioxidant and dispersant, glass fiber reinforced modified polyolefin plastics are prepared through high-speed stirring and twin-screw extrusion granulation process.

Benefits of technology

The mechanical properties and flame retardant and fire-retardant properties of polyolefin plastics are significantly improved, allowing them to meet higher fire-retardant standards and maintain good performance in high temperature environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of polyolefin plastics, and specifically to a glass fiber reinforced modified polyolefin plastic and a preparation method thereof, which is used to solve the problem that the existing glass fiber reinforced modified polyolefin plastic has poor mechanical strength and flame retardant and fireproof performance, which limits its application in some high-performance fields; the preparation method adds organic phosphorus nitrogen modified glass fiber as a reinforcing agent to the polyolefin resin, so that the polyolefin plastic not only has a significant improvement in mechanical properties, but also can maintain good performance under high temperature environment, and the flame retardant performance and fireproof grade are significantly improved, so that it can meet higher fireproof standards. At the same time, the preparation method adopts reasonable production process and technical means to ensure the good combination of glass fiber and polyolefin materials, thereby realizing the comprehensive optimization of plastic performance, significantly improving the performance and application range of polyolefin plastics, and meeting the needs of high-performance applications under various complex environmental conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyolefin plastics, and in particular to a glass fiber reinforced modified polyolefin plastic and a preparation method thereof. Background Art

[0002] As a widely used general-purpose plastic, polyolefin plastic has the advantages of good chemical stability, corrosion resistance, electrical insulation and processing performance. However, the mechanical strength of polyolefin plastic is relatively low, and its flame retardancy and heat resistance are poor, which limits its application in some high-performance fields. Glass fiber, as a high-performance reinforcing material, has the advantages of high strength and high modulus. Compounding it with polyolefin plastic can significantly improve the mechanical strength of polyolefin plastic. However, due to the "wick effect" produced by glass fiber, the combustion of polyolefin plastic becomes more intense.

[0003] Therefore, developing a glass fiber reinforced modified polyolefin plastic and a preparation method thereof is of great practical significance for improving the mechanical strength and flame retardant properties of polyolefin plastics. Summary of the invention

[0004] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a glass fiber reinforced modified polyolefin plastic and a preparation method thereof, which solves the problem that the existing glass fiber reinforced modified polyolefin plastic has poor mechanical strength and flame retardant properties, limiting its application in some high-performance fields.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A glass fiber reinforced modified polyolefin plastic comprises the following components in parts by weight:

[0007] 35-45 parts of polyolefin resin, 12-26 parts of organic phosphorus-nitrogen modified glass fiber, 3-7 parts of compatibilizer, 0.3-0.7 parts of lubricant, 0.3-0.7 parts of antioxidant and 0.1-0.3 parts of dispersant;

[0008] Wherein, the organic phosphorus-nitrogen modified glass fiber is prepared by the following steps:

[0009] Step s1: placing the glass fiber in a muffle furnace, calcining it at a temperature of 500-520° C. for 1.5-2.5 hours, then cooling it with the furnace, adding it to the mixed solution and soaking it for 3-5 hours, then centrifuging it, washing the precipitate with distilled water for 3-5 times, and then placing it in a vacuum drying oven and drying it at a temperature of 80-85° C. for 2-3 hours to obtain pretreated glass fiber;

[0010] Step s2: Add ferric nitrate nonahydrate, urea and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add pretreated glass fiber and continue stirring and reacting for 2-3 hours at a temperature of 55-60°C. After the reaction, cool the reaction product to room temperature, then place it in a vacuum drying oven, dry it at a temperature of 100-105°C for 2-3 hours, then place it in a muffle furnace, calcine it at a temperature of 350-400°C for 3-4 hours, and then cool it with the furnace to obtain loaded glass fiber;

[0011] Step s3: adding melamine, benzaldehyde and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introducing nitrogen protection, stirring the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 5-10min, then heating to 85-90°C and continuing to stir the reaction for 5-6h. After the reaction is completed, the reaction product is cooled to room temperature, then vacuum filtered, and the filter cake is washed with saturated brine and distilled water for 3-5 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 60-65°C for 2-3h to obtain a Schiff base intermediate;

[0012] Step s4: Add the Schiff base intermediate, phosphorous acid, dimethyl phosphite and N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 10-15 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 60-65°C and continue to stir and react for 1-2 hours, then heat to reflux and continue to stir and react for 3-4 hours, after the reaction is completed, cool the reaction product to room temperature, then rotary evaporate to remove the solvent, then wash with anhydrous ethanol 3-5 times, then place in a vacuum drying oven, and dry at a temperature of 60-65°C for 2-3 hours to obtain an organic phosphorus nitrogen intermediate;

[0013] Step s5: adding the organic phosphorus nitrogen intermediate, triethylamine and anhydrous tetrahydrofuran to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introducing nitrogen protection, stirring and reacting for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then adding isocyanatepropyltriethoxysilane solution dropwise while stirring, controlling the dropping rate to 1-2 drops / s, and continuing to stir and react for 10-15 hours under the condition of heating to 90-100°C after the dropwise addition is completed. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then separated and purified by silica gel column chromatography using a mixed solvent as an eluent to obtain a glass fiber modifier;

[0014] Step s6: Add the glass fiber modifier, deionized water and anhydrous ethanol to a three-necked flask equipped with an agitator, a thermometer and a reflux condenser, and stir the reaction for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 400-500r / min. Then add the loaded glass fiber and continue stirring the reaction for 8-10 hours under the condition of raising the temperature to reflux. After the reaction, cool the reaction product to room temperature and then centrifuge it. Wash the precipitate with anhydrous methanol for 3-5 times, and then place it in a vacuum drying oven and dry it at a temperature of 40-45°C for 4-5 hours to obtain organic phosphorus nitrogen modified glass fiber.

[0015] As a further solution of the present invention: the usage ratio of the glass fiber and the mixed solution in step s1 is 1 g: 8-10 mL.

[0016] As a further solution of the present invention: the glass fiber in step s1 is ECS305K-4.5mm chopped glass fiber; the mixed solution is a mixture of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 7:1-3; the mass fraction of the concentrated sulfuric acid is 98%; and the mass fraction of the hydrogen peroxide is 30%.

[0017] As a further solution of the present invention: the usage ratio of the ferric nitrate nonahydrate, urea, anhydrous ethanol and pretreated glass fiber in step s2 is 10 mmol: 0.05-0.09 g: 50-60 mL: 3 g.

[0018] As a further solution of the present invention: the usage ratio of melamine, benzaldehyde and anhydrous ethanol in step s3 is 10 mmol: 15-25 mmol: 60-70 mL.

[0019] As a further solution of the present invention: the usage ratio of the Schiff base intermediate, phosphorous acid, dimethyl phosphite and N,N-dimethylformamide in step s4 is 10 g: 10-20 mmol: 15-30 mmol: 100-120 mL.

[0020] As a further solution of the present invention: the usage ratio of the organic phosphorus nitrogen intermediate, triethylamine, anhydrous tetrahydrofuran and isocyanatepropyltriethoxysilane solution in step s5 is 10g:0.1-0.2g:100-120mL:15-20mL.

[0021] As a further solution of the present invention: the isocyanate propyl triethoxysilane solution in step s5 is a solution formed by dissolving isocyanate propyl triethoxysilane in anhydrous tetrahydrofuran at a ratio of 1.5-3.5 mL:15 mL.

[0022] As a further solution of the present invention: the usage ratio of the glass fiber modifier, deionized water, anhydrous ethanol and loaded glass fiber in step s6 is 3-11 g: 25-35 mL: 90-110 mL: 10 g.

[0023] As a further solution of the present invention: a method for preparing glass fiber reinforced modified polyolefin plastics, comprising the following steps:

[0024] Step 1: Weigh 35-45 parts of polyolefin resin, 12-26 parts of organic phosphorus nitrogen modified glass fiber, 3-7 parts of compatibilizer, 0.3-0.7 parts of lubricant, 0.3-0.7 parts of antioxidant and 0.1-0.3 parts of dispersant according to weight parts, and set aside;

[0025] Step 2: Add polyolefin resin, organic phosphorus nitrogen modified glass fiber, compatibilizer, lubricant, antioxidant and dispersant into a high-speed mixer, stir and mix for 5-15 minutes at a stirring rate of 800-1000r / min, then add into a twin-screw extruder, extrude and granulate at an extrusion temperature of 180-220°C and a screw speed of 200-400r / min to obtain glass fiber reinforced modified polyolefin plastic.

[0026] As a further solution of the present invention: the polyolefin resin is polypropylene; the polypropylene is PPYPJ-1215C produced by Sinopec Yangzi.

[0027] As a further solution of the present invention: the compatibilizer is one of PP-g-ST and PP-g-MAH.

[0028] As a further solution of the present invention: the lubricant is one of calcium stearate, zinc stearate and magnesium stearate.

[0029] As a further solution of the present invention: the antioxidant is one of antioxidant 168, antioxidant 1010 and antioxidant 1076.

[0030] As a further solution of the present invention: the dispersant is dispersant E525.

[0031] Beneficial effects of the present invention:

[0032] The present invention discloses a glass fiber reinforced modified polyolefin plastic and a preparation method thereof. The glass fiber reinforced modified polyolefin plastic is obtained by adding polyolefin resin, organic phosphorus nitrogen modified glass fiber, compatibilizer, lubricant, antioxidant and dispersant into a high-speed mixer, stirring and mixing, and then adding into a twin-screw extruder for extrusion granulation. The preparation method adds a specific proportion of organic phosphorus nitrogen modified glass fiber as a reinforcing agent into the polyolefin resin, so that the polyolefin plastic not only has a significant improvement in mechanical properties, but also can maintain good performance under high temperature environment, and the flame retardant performance and fireproof grade are significantly improved, so that it can meet higher fireproof standards. At the same time, the preparation method adopts reasonable production processes and technical means to ensure the good combination of glass fiber and polyolefin materials, thereby realizing the comprehensive optimization of plastic performance, significantly improving the performance and application range of polyolefin plastics, and meeting the needs of high-performance applications under various complex environmental conditions.

[0033] In the process of preparing glass fiber reinforced modified polyolefin plastic, an organic phosphorus-nitrogen modified glass fiber is first prepared. First, the glass fiber is subjected to acid oxidation treatment using a mixed solution to remove impurities on the surface of the glass fiber while improving the surface roughness, and introducing a large number of oxygen-containing groups to obtain pretreated glass fiber. Then, nonahydrated iron nitrate is used as a raw material to load a large amount of iron oxide on the surface of the pretreated glass fiber to obtain loaded glass fiber. Then, melamine and benzaldehyde are reacted, and part of the amino groups on the melamine react with the aldehyde groups on the benzaldehyde to form a Schiff base structure to obtain a Schiff base intermediate. Then, the Schiff base intermediate and phosphorous acid are reacted. , dimethyl phosphite, the Schiff base structure on the Schiff base intermediate reacts with phosphorous acid and PH on dimethyl phosphite to introduce a large number of organic phosphorus structures to obtain an organic phosphorus nitrogen intermediate, then the organic phosphorus nitrogen intermediate and isocyanate propyl triethoxysilane react, the amino group on the organic phosphorus nitrogen intermediate reacts with the isocyanate group on isocyanate propyl triethoxysilane to introduce a large number of siloxane groups to obtain a glass fiber modifier, and finally the glass fiber modifier is used to modify the loaded glass fiber, and the siloxane on the glass fiber modifier is hydrolyzed to form silanol, which can be grafted on the surface of the loaded glass fiber to perform a The organic phosphorus-nitrogen modified glass fiber has excellent compatibility, improves the compatibility between the glass fiber and the polyolefin resin, enables the two to be better combined, reduces interface defects, and thus improves the overall performance of the polyolefin plastic. Moreover, after the introduced iron oxide loads the glass fiber, the iron oxide can be used as a high-temperature resistant heat-insulating layer to protect the glass fiber, thereby improving the "candle wick effect" caused by the glass fiber. At the same time, the iron oxide can catalyze the polyolefin plastic to form a carbon layer at high temperature. The carbon layer covers the surface of the material and can isolate oxygen and heat. At the same time, during the combustion process, oxygen Ferrous chloride can capture free radicals produced by combustion, thereby interrupting the combustion chain reaction, which helps to reduce the combustion rate or even stop the combustion reaction completely, thereby improving the flame retardant and fireproof properties of polyolefin plastics. At the same time, a large amount of organic phosphorus and nitrogen structures are introduced. The phosphorus element decomposes at high temperature to generate phosphoric acid-containing substances, which promote the dehydration and carbonization of polyolefin plastics and further promote the formation of carbon layers. The nitrogen element will form non-combustible gases such as N2 and NH3 at high temperatures to dilute the oxygen and combustible gas concentration in the flame, while taking away some heat and reducing the combustion temperature. Therefore, the synergistic effect of these two elements can significantly improve the flame retardant and fireproof effects of polyolefin plastics. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Embodiment 1: This embodiment is a method for preparing a glass fiber reinforced modified polyolefin plastic, comprising the following steps:

[0036] Step A1: 1 g of ECS305K-4.5 mm chopped glass fiber was placed in a muffle furnace, calcined at 500° C. for 1.5 h, then cooled with the furnace, added to 8 mL of a mixed solution of 98% concentrated sulfuric acid and 30% hydrogen peroxide in a volume ratio of 7:1, and immersed for 3 h, then centrifuged, and the precipitate was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at 80° C. for 2 h to obtain pretreated glass fiber;

[0037] Step A2: 10 mmol of ferric nitrate nonahydrate, 0.05 g of urea and 50 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then 3 g of pretreated glass fiber was added and the mixture was heated to 55° C. and stirred for reaction for 2 h. After the reaction, the reaction product was cooled to room temperature, and then placed in a vacuum drying oven, dried at a temperature of 100° C. for 2 h, and then placed in a muffle furnace, calcined at a temperature of 350° C. for 3 h, and then cooled with the furnace to obtain a loaded glass fiber;

[0038] Step A3: 10 mmol melamine, 15 mmol benzaldehyde and 60 mL anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The reaction was stirred at 25° C. and a stirring rate of 300 r / min for 5 min, and then the temperature was raised to 85° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with saturated brine and distilled water for 3 times in sequence, and then placed in a vacuum drying oven and dried at 60° C. for 2 h to obtain a Schiff base intermediate;

[0039] Step A4: 10 g of Schiff base intermediate, 10 mmol of phosphorous acid, 15 mmol of dimethyl phosphite and 100 mL of N, N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 25° C. and a stirring rate of 300 r / min for 10 min, and then the mixture was heated to 60° C. and the stirring reaction was continued for 1 h. The mixture was heated to reflux and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then washed with anhydrous ethanol for 3 times, and then placed in a vacuum drying oven and dried at 60° C. for 2 h to obtain an organic phosphorus nitrogen intermediate.

[0040] Step A5: 10 g of the organic phosphorus nitrogen intermediate, 0.1 g of triethylamine and 100 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. The reaction was stirred for 20 min at a temperature of 25° C. and a stirring rate of 300 r / min. Then, 15 mL of an isocyanatepropyl triethoxysilane solution formed by dissolving isocyanatepropyl triethoxysilane in anhydrous tetrahydrofuran at a ratio of 1.5 mL:15 mL was added dropwise while stirring. The dropping rate was controlled to be 1 drop / s. After the addition was completed, the temperature was raised to 90° C. and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. Then, a silica gel column chromatography method was used to separate and purify the mixed solvent as an eluent to obtain a glass fiber modifier;

[0041] Step A6: 3 g of glass fiber modifier, 25 mL of deionized water and 90 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 20 min. Then, 10 g of loaded glass fiber was added and the temperature was raised to reflux and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed 3 times with anhydrous methanol and then placed in a vacuum drying oven and dried at a temperature of 40° C. for 4 h to obtain an organic phosphorus nitrogen modified glass fiber;

[0042] Step A7: 35 parts of polyolefin resin, 12 parts of organic phosphorus nitrogen modified glass fiber, 3 parts of compatibilizer, 0.3 parts of lubricant, 0.3 parts of antioxidant and 0.1 parts of dispersant are weighed in parts by weight for later use; the polyolefin resin is a polypropylene of Sinopec Yangzi with a model of PP YPJ-1215C; the compatibilizer is PP-g-ST; the lubricant is calcium stearate; the antioxidant is antioxidant 168; and the dispersant is dispersant E525;

[0043] Step A8: Add polyolefin resin, organic phosphorus nitrogen modified glass fiber, compatibilizer, lubricant, antioxidant and dispersant into a high-speed mixer, stir and mix for 5 minutes at a stirring rate of 800 r / min, then add into a twin-screw extruder, extrude and granulate at an extrusion temperature of 180°C and a screw speed of 200 r / min to obtain glass fiber reinforced modified polyolefin plastic.

[0044] Embodiment 2: This embodiment is a method for preparing a glass fiber reinforced modified polyolefin plastic, comprising the following steps:

[0045] Step A1: 1 g of ECS305K-4.5 mm chopped glass fiber was placed in a muffle furnace, calcined at a temperature of 510° C. for 2 h, then cooled with the furnace, added to a mixed solution of 9 mL of 98% concentrated sulfuric acid and 30% hydrogen peroxide in a volume ratio of 7:2, and immersed for 4 h, then centrifuged, and the precipitate was washed with distilled water 4 times, and then placed in a vacuum drying oven and dried at a temperature of 82° C. for 2.5 h to obtain pretreated glass fiber;

[0046] Step A2: 10 mmol of ferric nitrate nonahydrate, 0.07 g of urea and 55 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then 3 g of pretreated glass fiber was added and the mixture was heated to 58° C. and stirred for reaction for 2.5 h. After the reaction, the reaction product was cooled to room temperature, and then placed in a vacuum drying oven, dried at a temperature of 102° C. for 2.5 h, and then placed in a muffle furnace, calcined at a temperature of 375° C. for 3.5 h, and then cooled with the furnace to obtain a loaded glass fiber;

[0047] Step A3: 10 mmol melamine, 20 mmol benzaldehyde and 65 mL anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The reaction was stirred at a temperature of 28° C. and a stirring rate of 350 r / min for 7 min, and then the temperature was raised to 88° C. and the stirring reaction was continued for 5.5 h. After the reaction was completed, the reaction product was cooled to room temperature and then vacuum filtered. The filter cake was washed with saturated brine and distilled water for 4 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 62° C. for 2.5 h to obtain a Schiff base intermediate;

[0048] Step A4: 10 g of Schiff base intermediate, 15 mmol of phosphorous acid, 22 mmol of dimethyl phosphite and 110 mL of N, N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 28° C. and a stirring rate of 350 r / min for 12 min, and then the mixture was heated to 62° C. and the stirring reaction was continued for 1.5 h. The mixture was heated to reflux and the stirring reaction was continued for 3.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then washed with anhydrous ethanol 4 times, and then placed in a vacuum drying oven and dried at 62° C. for 2.5 h to obtain an organic phosphorus nitrogen intermediate;

[0049] Step A5: 10 g of the organic phosphorus nitrogen intermediate, 0.15 g of triethylamine and 110 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. The reaction was stirred for 25 min at a temperature of 28° C. and a stirring rate of 350 r / min. Then, 18 mL of isocyanatepropyl triethoxysilane solution formed by dissolving isocyanatepropyl triethoxysilane in anhydrous tetrahydrofuran at a ratio of 2.5 mL:15 mL was added dropwise while stirring. The dropping rate was controlled to be 1 drop / s. After the addition was completed, the temperature was raised to 95° C. and the stirring reaction was continued for 12 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. Then, a silica gel column chromatography method was used to separate and purify the mixed solvent as an eluent to obtain a glass fiber modifier;

[0050] Step A6: 7 g of glass fiber modifier, 30 mL of deionized water and 100 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 28° C. and a stirring rate of 450 r / min for 25 min. Then, 10 g of loaded glass fiber was added and the temperature was raised to reflux and the stirring reaction was continued for 9 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed 4 times with anhydrous methanol and then placed in a vacuum drying oven and dried at a temperature of 42° C. for 4.5 h to obtain an organic phosphorus nitrogen modified glass fiber;

[0051] Step A7: Weigh 40 parts of polyolefin resin, 19 parts of organic phosphorus nitrogen modified glass fiber, 5 parts of compatibilizer, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.2 parts of dispersant according to weight parts for later use; the polyolefin resin is a polypropylene of Sinopec Yangzi with model PP YPJ-1215C; the compatibilizer is PP-g-ST; the lubricant is zinc stearate; the antioxidant is antioxidant 1010; the dispersant is dispersant E525;

[0052] Step A8: Add polyolefin resin, organic phosphorus nitrogen modified glass fiber, compatibilizer, lubricant, antioxidant and dispersant into a high-speed mixer, stir and mix for 10 minutes at a stirring rate of 900 r / min, then add into a twin-screw extruder, extrude and granulate at an extrusion temperature of 200°C and a screw speed of 300 r / min to obtain glass fiber reinforced modified polyolefin plastic.

[0053] Embodiment 3: This embodiment is a method for preparing a glass fiber reinforced modified polyolefin plastic, comprising the following steps:

[0054] Step A1: 1 g of ECS305K-4.5 mm chopped glass fiber was placed in a muffle furnace, calcined at a temperature of 520° C. for 2.5 h, then cooled with the furnace, added to a mixed solution of 10 mL of 98% concentrated sulfuric acid and 30% hydrogen peroxide in a volume ratio of 7:3, and immersed for 5 h, then centrifuged, and the precipitate was washed with distilled water for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 h to obtain pretreated glass fiber;

[0055] Step A2: 10 mmol of ferric nitrate nonahydrate, 0.09 g of urea and 60 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min. Then, 3 g of pretreated glass fiber was added and the mixture was heated to 60° C. and stirred for 3 h. After the reaction, the reaction product was cooled to room temperature, and then placed in a vacuum drying oven and dried at a temperature of 105° C. for 3 h. Then, the mixture was placed in a muffle furnace and calcined at a temperature of 400° C. for 4 h. Then, the mixture was cooled with the furnace to obtain a loaded glass fiber.

[0056] Step A3: 10 mmol melamine, 25 mmol benzaldehyde and 70 mL anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The reaction was stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 10 min, and then the temperature was raised to 90° C. and the stirring reaction was continued for 6 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with saturated brine and distilled water for 5 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain a Schiff base intermediate;

[0057] Step A4: 10 g of Schiff base intermediate, 20 mmol of phosphorous acid, 30 mmol of dimethyl phosphite and 120 mL of N, N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 30° C. and a stirring rate of 400 r / min for 15 min, and then the mixture was heated to 65° C. and continued to stir for reaction for 2 h, and then the mixture was heated to reflux and continued to stir for reaction for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation, and then the mixture was washed with anhydrous ethanol for 5 times, and then placed in a vacuum drying oven and dried at 65° C. for 3 h to obtain an organic phosphorus nitrogen intermediate;

[0058] Step A5: 10 g of the organic phosphorus nitrogen intermediate, 0.2 g of triethylamine and 120 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then 20 mL of an isocyanatepropyl triethoxysilane solution prepared by dissolving 3.5 mL:15 mL of isocyanatepropyl triethoxysilane in anhydrous tetrahydrofuran was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the addition was completed, the mixture was heated to 100° C. and the stirring reaction was continued for 15 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. Then, a silica gel column chromatography method was used to separate and purify the mixture using a mixed solvent as an eluent to obtain a glass fiber modifier;

[0059] Step A6: 11 g of glass fiber modifier, 35 mL of deionized water and 110 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred for 30 min at a temperature of 30° C. and a stirring rate of 500 r / min. Then, 10 g of loaded glass fiber was added and the mixture was heated to reflux and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed with anhydrous methanol 5 times, and then placed in a vacuum drying oven and dried at a temperature of 45° C. for 5 h to obtain an organic phosphorus-nitrogen modified glass fiber;

[0060] Step A7: 45 parts of polyolefin resin, 26 parts of organic phosphorus nitrogen modified glass fiber, 7 parts of compatibilizer, 0.7 parts of lubricant, 0.7 parts of antioxidant and 0.3 parts of dispersant are weighed according to weight parts for use; the polyolefin resin is a polypropylene of Sinopec Yangzi with model PP YPJ-1215C; the compatibilizer is PP-g-MAH; the lubricant is magnesium stearate; the antioxidant is antioxidant 1076; the dispersant is dispersant E525;

[0061] Step A8: Add polyolefin resin, organic phosphorus nitrogen modified glass fiber, compatibilizer, lubricant, antioxidant and dispersant into a high-speed mixer, stir and mix for 15 minutes at a stirring rate of 1000 r / min, then add into a twin-screw extruder, extrude and granulate at an extrusion temperature of 220°C and a screw speed of 400 r / min to obtain glass fiber reinforced modified polyolefin plastic.

[0062] Comparative Example 1:

[0063] This comparative example is a method for preparing a glass fiber reinforced modified polyolefin plastic, comprising the following steps:

[0064] Step A1: 45 parts of polyolefin resin, 7 parts of compatibilizer, 0.7 parts of lubricant, 0.7 parts of antioxidant and 0.3 parts of dispersant are weighed in parts by weight for later use; the polyolefin resin is a polypropylene of Sinopec Yangzi with a model of PP YPJ-1215C; the compatibilizer is PP-g-MAH; the lubricant is magnesium stearate; the antioxidant is antioxidant 1076; and the dispersant is dispersant E525;

[0065] Step A2: Add polyolefin resin, compatibilizer, lubricant, antioxidant and dispersant into a high-speed mixer, stir and mix for 15 minutes at a stirring rate of 1000 r / min, then add into a twin-screw extruder, extrude and granulate at an extrusion temperature of 220°C and a screw speed of 400 r / min to obtain glass fiber reinforced modified polyolefin plastic.

[0066] Comparative Example 2:

[0067] This comparative example is a method for preparing a glass fiber reinforced modified polyolefin plastic, comprising the following steps:

[0068] Step A1: 45 parts of polyolefin resin, 26 parts of ECS305K-4.5mm chopped glass fibers, 7 parts of compatibilizer, 0.7 parts of lubricant, 0.7 parts of antioxidant and 0.3 parts of dispersant are weighed in parts by weight for later use; the polyolefin resin is a polypropylene of Sinopec Yangzi with a model of PPYPJ-1215C; the compatibilizer is PP-g-MAH; the lubricant is magnesium stearate; the antioxidant is antioxidant 1076; and the dispersant is dispersant E525;

[0069] Step A2: Add polyolefin resin, ECS305K-4.5mm chopped glass fiber, compatibilizer, lubricant, antioxidant and dispersant into a high-speed mixer, stir and mix for 15 minutes at a stirring rate of 1000 r / min, then add into a twin-screw extruder, extrude and granulate at an extrusion temperature of 220°C and a screw speed of 400 r / min to obtain glass fiber reinforced modified polyolefin plastic.

[0070] Comparative Example 3:

[0071] This comparative example is a method for preparing a glass fiber reinforced modified polyolefin plastic, comprising the following steps:

[0072] Step A1: 1 g of ECS305K-4.5 mm chopped glass fiber was placed in a muffle furnace, calcined at a temperature of 520° C. for 2.5 h, then cooled with the furnace, added to a mixed solution of 10 mL of 98% concentrated sulfuric acid and 30% hydrogen peroxide in a volume ratio of 7:3, and immersed for 5 h, then centrifuged, and the precipitate was washed with distilled water for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 h to obtain pretreated glass fiber;

[0073] Step A2: 10 mmol of ferric nitrate nonahydrate, 0.09 g of urea and 60 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min. Then, 3 g of pretreated glass fiber was added and the mixture was heated to 60° C. and stirred for 3 h. After the reaction, the reaction product was cooled to room temperature, and then placed in a vacuum drying oven and dried at a temperature of 105° C. for 3 h. Then, the mixture was placed in a muffle furnace and calcined at a temperature of 400° C. for 4 h. Then, the mixture was cooled with the furnace to obtain a loaded glass fiber.

[0074] Step A3: 45 parts of polyolefin resin, 26 parts of loaded glass fiber, 7 parts of compatibilizer, 0.7 parts of lubricant, 0.7 parts of antioxidant and 0.3 parts of dispersant are weighed in parts by weight for later use; the polyolefin resin is a polypropylene of Sinopec Yangzi with a model of PP YPJ-1215C; the compatibilizer is PP-g-MAH; the lubricant is magnesium stearate; the antioxidant is antioxidant 1076; and the dispersant is dispersant E525;

[0075] Step A4: Add polyolefin resin, loaded glass fiber, compatibilizer, lubricant, antioxidant and dispersant into a high-speed mixer, stir and mix for 15 minutes at a stirring rate of 1000 r / min, then add into a twin-screw extruder, extrude and granulate at an extrusion temperature of 220°C and a screw speed of 400 r / min to obtain glass fiber reinforced modified polyolefin plastic.

[0076] Comparative Example 4:

[0077] This comparative example is a method for preparing a glass fiber reinforced modified polyolefin plastic, comprising the following steps:

[0078] Step A1: 1 g of ECS305K-4.5 mm chopped glass fiber was placed in a muffle furnace, calcined at a temperature of 520° C. for 2.5 h, then cooled with the furnace, added to a mixed solution of 10 mL of 98% concentrated sulfuric acid and 30% hydrogen peroxide in a volume ratio of 7:3, and immersed for 5 h, then centrifuged, and the precipitate was washed with distilled water for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 h to obtain pretreated glass fiber;

[0079] Step A2: 10 mmol of ferric nitrate nonahydrate, 0.09 g of urea and 60 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min. Then, 3 g of pretreated glass fiber was added and the mixture was heated to 60° C. and stirred for 3 h. After the reaction, the reaction product was cooled to room temperature, and then placed in a vacuum drying oven and dried at a temperature of 105° C. for 3 h. Then, the mixture was placed in a muffle furnace and calcined at a temperature of 400° C. for 4 h. Then, the mixture was cooled with the furnace to obtain a loaded glass fiber.

[0080] Step A3: 11 g of isocyanatepropyltriethoxysilane, 35 mL of deionized water and 110 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred for 30 min at a temperature of 30° C. and a stirring rate of 500 r / min. Then, 10 g of loaded glass fiber was added and the mixture was heated to reflux and stirred for 10 h. After the reaction, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed 5 times with anhydrous methanol and then placed in a vacuum drying oven and dried at a temperature of 45° C. for 5 h to obtain a modified glass fiber.

[0081] Step A4: 45 parts of polyolefin resin, 26 parts of modified glass fiber, 7 parts of compatibilizer, 0.7 parts of lubricant, 0.7 parts of antioxidant and 0.3 parts of dispersant are weighed in parts by weight for later use; the polyolefin resin is a polypropylene of Sinopec Yangzi with a model of PP YPJ-1215C; the compatibilizer is PP-g-MAH; the lubricant is magnesium stearate; the antioxidant is antioxidant 1076; and the dispersant is dispersant E525;

[0082] Step A5: Add polyolefin resin, modified glass fiber, compatibilizer, lubricant, antioxidant and dispersant into a high-speed mixer, stir and mix for 15 minutes at a stirring rate of 1000 r / min, then add into a twin-screw extruder, extrude and granulate at an extrusion temperature of 220°C and a screw speed of 400 r / min to obtain glass fiber reinforced modified polyolefin plastic.

[0083] The glass fiber reinforced modified polyolefin plastics of Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests, and the test method was as follows:

[0084] According to the test standard ISO 527-2019, the tensile properties of the specimens with a size of 170×10×4mm were tested, wherein the tensile speed was 50mm / min and the test temperature was 23°C; according to the test standard ISO 178-2019, the bending properties of the specimens with a size of 80×10×4mm were tested, wherein the bending test speed was 2mm / min, the deflection was 6mm, and the test temperature was 23°C; according to the test standard GB / T2408-2008, the vertical burning grade of the specimens with a size of 125×12.5×3.2mm was determined; according to the test standard GB / T2406-2008 and using the JF-3 oxygen index tester, the limiting oxygen index test was carried out on the specimens with a size of 80×10×4mm.

[0085] The test results are shown in the following table:

[0086] .

[0087] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be known that adding organic phosphorus-nitrogen modified glass fibers can greatly improve the mechanical properties of polyolefin plastics, and at the same time, its flame retardant properties are greatly improved.

[0088] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0089] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined in this application, they shall all fall within the protection scope of the present invention.

Claims

1. A glass fiber reinforced modified polyolefin plastic, characterized in that: It comprises the following components in parts by weight: 35-45 parts of polyolefin resin, 12-26 parts of organic phosphorus-nitrogen modified glass fiber, 3-7 parts of compatibilizer, 0.3-0.7 parts of lubricant, 0.3-0.7 parts of antioxidant and 0.1-0.3 parts of dispersant; Wherein, the organic phosphorus-nitrogen modified glass fiber is prepared by the following steps: Step s1: placing the glass fiber in a muffle furnace, calcining it at a temperature of 500-520°C for 1.5-2.5h, cooling it with the furnace, adding it to a mixed solution and soaking it for 3-5h, centrifuging it, washing the precipitate with distilled water for 3-5 times, and then placing it in a vacuum drying oven, drying it at a temperature of 80-85°C for 2-3h to obtain pretreated glass fiber; the amount ratio of the glass fiber to the mixed solution in step s1 is 1g:8-10m; the glass fiber is ECS305K-4.5mm chopped glass fiber; the mixed solution is a mixture of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 7:1-3; the mass fraction of the concentrated sulfuric acid is 98%; the mass fraction of the hydrogen peroxide is 30%; Step s2: adding ferric nitrate nonahydrate, urea and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introducing nitrogen protection, stirring and reacting for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then adding pretreated glass fiber and heating to 55-60°C and continuing to stir and react for 2-3 hours, after the reaction is completed, cooling the reaction product to room temperature, then placing it in a vacuum drying oven, drying it at a temperature of 100-105°C for 2-3 hours, then placing it in a muffle furnace, calcining it at a temperature of 350-400°C for 3-4 hours, and then cooling it with the furnace to obtain a loaded glass fiber; the amount ratio of the ferric nitrate nonahydrate, urea, anhydrous ethanol and pretreated glass fiber in step s2 is 10mmol:0.05-0.09g:50-60mL:3g; Step s3: adding melamine, benzaldehyde and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introducing nitrogen protection, stirring the reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 5-10 min, then heating to 85-90° C. and continuing to stir the reaction for 5-6 h. After the reaction is completed, the reaction product is cooled to room temperature, then vacuum filtered, and the filter cake is washed with saturated brine and distilled water for 3-5 times in sequence, then placed in a vacuum drying oven, and dried at a temperature of 60-65° C. for 2-3 h to obtain a Schiff base intermediate; the amount ratio of melamine, benzaldehyde and anhydrous ethanol in step s3 is 10 mmol: 15-25 mmol: 60-70 mL; Step s4: Add the Schiff base intermediate, phosphorous acid, dimethyl phosphite and N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, introduce nitrogen protection, stir and react for 10-15 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, then heat to 60-65° C. and continue to stir and react for 1-2 hours, then heat to reflux and continue to stir and react for 3- 4h, after the reaction is completed, the reaction product is cooled to room temperature, then the solvent is removed by rotary evaporation, then washed with anhydrous ethanol for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 60-65°C for 2-3h to obtain an organic phosphorus nitrogen intermediate; the amount ratio of the Schiff base intermediate, phosphorous acid, dimethyl phosphite and N, N-dimethylformamide in step s4 is 10g: 10-20mmol: 15-30mmol: 100-120mL; Step s5: Add the organic phosphorus nitrogen intermediate, triethylamine and anhydrous tetrahydrofuran to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add isocyanate propyl triethoxysilane solution dropwise while stirring, control the dropping rate to 1-2 drops / s, and continue stirring and reacting for 10-15 hours under the condition of heating to 90-100°C after the reaction. After the reaction is completed, The product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then the mixed solvent is used as an eluent for separation and purification by silica gel column chromatography to obtain a glass fiber modifier; the amount ratio of the organic phosphorus nitrogen intermediate, triethylamine, anhydrous tetrahydrofuran and isocyanate propyl triethoxysilane solution in step s5 is 10g: 0.1-0.2g: 100-120mL: 15-20mL; the isocyanate propyl triethoxysilane solution is a solution formed by dissolving isocyanate propyl triethoxysilane in anhydrous tetrahydrofuran at a ratio of 1.5-3.5mL: 15mL; Step s6: Add a glass fiber modifier, deionized water and anhydrous ethanol to a three-necked flask equipped with an agitator, a thermometer and a reflux condenser, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 400-500r / min, then add the loaded glass fiber and continue stirring and reacting for 8-10 hours under the condition of heating to reflux. After the reaction, cool the reaction product to room temperature and then centrifuge it. Wash the precipitate with anhydrous methanol for 3-5 times, then place it in a vacuum drying oven and dry it at a temperature of 40-45°C for 4-5 hours to obtain organic phosphorus nitrogen modified glass fiber; the amount ratio of the glass fiber modifier, deionized water, anhydrous ethanol and loaded glass fiber in step s6 is 3-11g:25-35mL:90-110mL:10g.

2. A method for preparing a glass fiber reinforced modified polyolefin plastic as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Weigh 35-45 parts of polyolefin resin, 12-26 parts of organic phosphorus nitrogen modified glass fiber, 3-7 parts of compatibilizer, 0.3-0.7 parts of lubricant, 0.3-0.7 parts of antioxidant and 0.1-0.3 parts of dispersant according to weight parts, and set aside; Step 2: Add polyolefin resin, organic phosphorus nitrogen modified glass fiber, compatibilizer, lubricant, antioxidant and dispersant into a high-speed mixer, stir and mix for 5-15 minutes at a stirring rate of 800-1000r / min, then add into a twin-screw extruder, extrude and granulate at an extrusion temperature of 180-220°C and a screw speed of 200-400r / min to obtain glass fiber reinforced modified polyolefin plastic.

3. The method for preparing a glass fiber reinforced modified polyolefin plastic according to claim 2, characterized in that: The polyolefin resin is polypropylene; the polypropylene is PP YPJ-1215C of Sinopec Yangzi; The compatibilizer is one of PP-g-ST and PP-g-MAH; The lubricant is one of calcium stearate, zinc stearate and magnesium stearate; The antioxidant is one of antioxidant 168, antioxidant 1010 and antioxidant 1076; The dispersant is dispersant E525.

Citation Information

Patent Citations

  • High-performance flame-retardant self-cleaning daylighting panel material easy to melt and break and free of dripping and production process thereof

    CN112592522A

  • Phosphorus-nitrogen triazine flame retardant containing P-C bond and preparation method thereof

    CN115417896A